Efektivitas Pengelolaan Dana Desa di Desa Pangada’a Kecamatan Dungaliyo Kabupaten Gorontalo - Sindi Djafar; Tri Handayani Amaliah; Siti Pratiwi Husain (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Effectiveness of Village Fund Management in Pangada'a Village, Dungaliyo District, Gorontalo Regency. Sindi Djafar. 931418121. 2024. Thesis. Accounting Study Program, Accounting Department, Faculty of Economics, Gorontalo State University.This study aims to: 1). to determine the effectiveness of village fund management in Pangada'a, Dungaliyo District, 2) to determine the supporting and inhibiting factors for the effectiveness of village fund management in Pangada'a, Dungaliyo District. The research method used is qualitative descriptive, the location of the study is in Pangada'a Village, Gorontalo Regency. Data collection techniques in the form of observation, interviews and documentation which are then analyzed using qualitative data based on the concepts of Miles and Huberman.The results of the study show: 1). Village fund management in Pangada'a, Dungaliyo District has been carried out but is not yet effective and still requires improvement in aspects of implementation and financial management (administration) and accountability for reporting village financial management to achieve optimal effectiveness. 2). Determining Factors of Effectiveness of Village Fund Management Pangada'a Sub-district has been proven to be a supporting factor in the implementation of effective village fund management, but is still constrained by the aspect of timeliness.